2002
DOI: 10.1034/j.1600-0838.2002.120111_2.x
|View full text |Cite
|
Sign up to set email alerts
|

Timing of post‐exercise protein intake is important for muscle hypertrophy with resistance training in elderly humans

Abstract: (1) Age‐associated loss of skeletal muscle mass and strength can partly be counteracted by resistance training, causing a net synthesis of muscular proteins. Protein synthesis is influenced synergistically by post‐exercise amino acid supplementation, but the importance of the timing of protein intake remains unresolved. (2) The study investigated the importance of immediate (P0) or delayed (P2) intake of an oral protein supplement upon muscle hypertrophy and strength over a period of resistance training in eld… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 17 publications
(20 reference statements)
1
10
0
1
Order By: Relevance
“…Since steeper muscle fibre pennation angle allows for a greater physiological fibre area for a given volume of muscle, the post-training increase in VL muscle fibre pennation angle alone may explain the present observation of disproportionate changes in physiological versus anatomical muscle CSA. In fact, previous studies that have examined the human quadriceps femoris muscle by combined muscle biopsy sampling and macroscopic muscle imaging techniques (MRI, CT) also have demonstrated the increase in muscle fibre CSA to be greater than that of anatomical muscle CSA with resistance training (Frontera et al 1988;Hakkinen et al 1998;Esmarck et al 2001). Unfortunately, fibre pennation angle was not obtained in any of these studies.…”
Section: Relationships Between Measures Of Muscle Morphology and Archmentioning
confidence: 58%
“…Since steeper muscle fibre pennation angle allows for a greater physiological fibre area for a given volume of muscle, the post-training increase in VL muscle fibre pennation angle alone may explain the present observation of disproportionate changes in physiological versus anatomical muscle CSA. In fact, previous studies that have examined the human quadriceps femoris muscle by combined muscle biopsy sampling and macroscopic muscle imaging techniques (MRI, CT) also have demonstrated the increase in muscle fibre CSA to be greater than that of anatomical muscle CSA with resistance training (Frontera et al 1988;Hakkinen et al 1998;Esmarck et al 2001). Unfortunately, fibre pennation angle was not obtained in any of these studies.…”
Section: Relationships Between Measures Of Muscle Morphology and Archmentioning
confidence: 58%
“…Many investigators who have examined the influence of Cr supplementation during resistance training in young subjects, generally reported significant increases in strength, lean tissue mass and body weight (23)(24)(25)(26)(27)(28)(29)(30)(31), however, there is the possibility that a given subject pool may contain non-responders (32). The findings of the current study do agree with Bermon et al (33) and Eijnde et al (34) who concluded that oral Cr supplementation did not provide additional benefits for fitness, maximal dynamic strength, or isometric endurance in healthy, elderly, male or female subjects, when accompanied by an effective strength training program.…”
Section: Discussionmentioning
confidence: 99%
“…The RTCr and the RTCrPr groups loaded 7 g of creatine monohydrate with 480 ml of the glucose solution (Gatorade™) on each of 3 days per week for the 2 weeks prior to the training intervention. Once training began, the RTP group consumed the placebo (480 ml of Gatorade™), the RTCr group consumed (5g Creatine with 480 ml Gatorade™), the RTPr group consumed (35g whey protein (Old Fashioned Natural Products, Santa Ana, CA) with 480 ml of Gatorade™), and the RTCrPr group consumed (5g creatine and 35g whey protein with 480 ml Gatorade™) immediately after each supervised training session (25). A research assistant administered supplementation and ensured that each subject completed the ingestion of their drink in a timely fashion following the completion of each training session.…”
Section: Dietary Analysis and Supplementation Protocolmentioning
confidence: 99%
“…Providing interventions for not only tongue muscles, but also jaw opening muscles, might be effective to prevent dysphagia and malnutrition. Furthermore, resistance training is effective for increasing muscle mass and improving muscle function . There are been various training exercises for the tongue muscle and jaw‐opening muscles that improve swallowing function .…”
Section: Discussionmentioning
confidence: 99%